If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3*x-(3x+5)=2*(x-2)-3
We simplify the equation to the form, which is simple to understand
3*x-(3x+5)=2*(x-2)-3
Simplifying:
+3x-(3x+5)=2*(x-2)-3
Remove unnecessary parentheses
+3x-3x-5=2*(x-2)-3
Reorder the terms in parentheses
+3x-3x-5=+(+2x-4)-3
Remove unnecessary parentheses
+3x-3x-5=+2x-4-3
We move all terms containing x to the left and all other terms to the right.
+3x-3x-2x=-4-3+5
We simplify left and right side of the equation.
-2x=-2
We divide both sides of the equation by -2 to get x.
x=1
| 56x^2+5x-6= | | 4*10+8= | | 0=12xy-18x+6-8y | | 2(2b-4)+14=6 | | 6x+11-2x=x+2x+16 | | 31g=g-26 | | 11x-18=-7 | | 4y+15=39 | | 6a+13=-5 | | 4x+7=-3x+21 | | 10x-7=40x+5 | | 3y+2=9x+8 | | 138-3x=33x+18 | | 9-7x=204-42x | | 5x+2+6=2x+28+x | | 3x-y+6x+7y= | | 15x+5=755 | | -5(b-7)-3b=-23 | | X+x^2=90 | | -5=2+w | | 2x+3x+4x= | | 11-9x=28-16x | | 8*(x-2)+16=7*(x+2) | | 3x+(-8)=-71 | | 3x-5x+x=10 | | 9x^2-2=0 | | 2x-4(x+2)=5x+6 | | 5x+6b=45 | | s=p+16 | | 4(3w-7)=32 | | x+1.1=8.1 | | -7u=-21 |